2020
DOI: 10.1145/3339904
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourcing moral machines

Abstract: A platform for creating a crowdsourced picture of human opinions on how machines should handle moral dilemmas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 21 publications
(18 reference statements)
1
35
0
Order By: Relevance
“…The ethical challenges facing AVs—especially the trolley-type dilemmas of protecting the passengers versus pedestrians—has been a topic of intense investigation as well as of debate. The highly publicized MME (Awad et al, 2018 ) and other prominent works (Rahwan, 2018 ; Awad et al, 2020a , b ) are based on the premise that EDs are a critical challenge to address for the consumer adoption of AVs. Not adequately addressing this issue could lead consumers to shun AVs, and thus nullify all their promised benefits (Bonnefon et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The ethical challenges facing AVs—especially the trolley-type dilemmas of protecting the passengers versus pedestrians—has been a topic of intense investigation as well as of debate. The highly publicized MME (Awad et al, 2018 ) and other prominent works (Rahwan, 2018 ; Awad et al, 2020a , b ) are based on the premise that EDs are a critical challenge to address for the consumer adoption of AVs. Not adequately addressing this issue could lead consumers to shun AVs, and thus nullify all their promised benefits (Bonnefon et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…Several scholars and manufacturers point out the near impossibility and frivolousness of solving this issue (De Frietas et al, 2020 ; 2021 ). On the other hand, behavioral science researchers consider public opinion as a necessary input in deciding about the ethical principles for AVs (Awad et al, 2018 , 2020a , b ). Many policy makers, such as the European Commission’s CAV2020 report have suggested that EDs can be adequately solved if AVs follow a continuous risk management process in its operation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these technological advancements, AV accidents cannot be entirely eliminated ( Goodall, 2014b ; Bonnefon et al, 2016 ; Guo et al, 2018 ; Nyholm and Smids, 2018 ). In this regard, AVs are among the first autonomous agents that make decisions with potential life-and-death consequences ( Awad et al, 2020 ). While vehicle accidents have existed, the introduction of AVs has shifted ethical implications during accidents Danielson (2015) , Shariff et al (2017) , Awad et al (2018a) , Taddeo & Floridi (2018) because humans and AVs make intrinsically different ethical decisions.…”
Section: Introductionmentioning
confidence: 99%